The forgotten competitive arena: Strategy in natural resource industries - Casarin, Ariel (2020)
Despite their importance in the global economy, the complex competitive dynamics of natural resource industries and their implications for business performance remain largely understudied in strategic management. This article identifies major traits that are highly relevant in natural resource industries, including the standardized nature of their products, their emphasis on process-based innovations, the presence of dual physical and financial derivative markets, and the importance of nonmarket forces that affect the creation and appropriation of rents from natural resources. We propose a general framework that guides our observations, and we discuss research opportunities for the study of firm strategy in natural resource industries.